An extension of advancing front technique on new target surface after virtual topology operations. (October 2018) - Wang, Wei; Fan, Hongzhou; Xi, Guang
Highlights: An extension of advancing front technique. Determining new target surface by geometric continuity. Improving advancing front technique based on new description of front configuration. Optimizes the mesh distribution according to the surfaces topology. Abstract: In this paper, an extension of advancing front technique (AFT) on new target surface (NTS) after virtual topology operations has been achieved in order to suitably represent CAD model and enhance the accuracy of numerical analyses. The extension of AFT has been accomplished through two stages. In the first stage, through analysis of the connection features of the intersecting lines with geometric continuity, a new notion of NTS is proposed. Based on the new notion, the topology of NTS is adjusted to generate meshes and meet the requirements of numerical analyses. In the second stage, AFT is extended accordingly in order to realize the topology of NTS. Specifically, based on the concise description of the front configuration of AFT, all of the subordinate aspects of AFT, including meshing order, generation of elements and nodes, and validity checking, are optimized. With the extension of AFT in this fashion, the target surfaces of AFT have been extended from the parametric surfaces to the composite surfaces. Finally, two examples are calculated with the extended AFT. The results of the calculation have verified that the topology of the composite surfaces is suitable and that the extended AFT is accurate and efficient.